Chemical and isotopic constraints on fluid origin and genesis of geothermal systems in the Tingri-Tangra Yumco rift, southern Tibetan Plateau - Wei Liu; Maoliang Zhang; Yi Liu; Lifeng Cui; Yuji Sano; Sheng Xu (Geothermal Energy, 2024)
Abstract Numerous geothermal systems are hosted by extensional rifts that transect the Himalayas and Lhasa block in the Himalayan–Tibetan orogen. However, the relationships between hydrogeological processes and geothermal fluid circulation in different tectonic units remain unclear. Here, we report an integrated dataset of chemical and isotopic compositions (including major and trace elements, δD, δ18O, and 87Sr/86Sr) of thermal spring water from the Tingri-Tangra Yumco rift to assess their origins and circulation processes. δ18O (− 21.3 to − 17.0‰) and δD (− 166 to − 135‰) values of thermal springs indicate dominant recharge of meteoric waters from areas with elevation of > 6000 m and minor addition of magmatic fluids. Meteoric water could infiltrate to depths of about 1700–2900 m along the faults, whereby it is influenced by geothermal gradient and/or conductive heat transfer of magmatic fluids. The thermal spring waters are mainly Na-HCO3 type and are controlled by dissolution of silicate and carbonate minerals and mixing with deep fluids. The results of chemical and multicomponent geothermometers indicate reservoir temperatures of 115 − 195 ℃, corresponding to a convection heat flux of 3.96 × 105 J/s to 1.78 × 107 J/s from geothermal systems, which are comparable to that of the low-enthalpy geothermal systems in southern Italy. Geochemical modeling is conducted to assess the water–mineral equilibria in the reservoir. Trace elements and 87Sr/86Sr data suggest spatially variable controlling factors for the rift-related geothermal systems: (1) interaction with granitoid and carbonate in the Himalayas; (2) cold groundwater mixing with that leaching from granite and volcanic rocks in the Lhasa block; (3) the input of vapors from magmatic degassing. The geochemistry of thermal springs associated with extensional rift is largely induced by the interaction between fluid and different reservoir rocks in the Himalayas and Lhasa block. Based on these findings, a genetic model is proposed for exploration and development of geothermal resources in the Tingri-Tangra Yumco rift.